STUDI LITERATUR REVIEW TERHADAP PENELITIAN EARNINGS RESPONSE CEOFFICIENT - Calvin Restu Junior Sungloria; C. Chinthya; Devin Rivario; Luis Gunawan (Faculty of Economics and Business, Universitas Warmadewa, 2022)
This literature study was conducted to evaluate previous research using variables that affect the earnings response coefficient. The earnings response coefficient is a measuring tool that shows the market response to earnings information provided by the company. Because there are factors that affect the earnings response coefficient, what is used in this study is growth opportunity, leverage, earnings persistence, and firm size. The research was conducted using a literature study method that examined and analyzed articles related to earnings response coefficients. To increase investor confidence and increase market reaction to the company, the company must have a small leverage and must increase growth opportunity, company size and earnings persistence. The research shows that growth opportunity and leverage has a negative effect on the earnings response coefficient. However earnings persistence and firm size have an impact or influence on the earnings response coefficient